Job Demands-Control model and employees mental health: The mediate role of work-family conflict - Chambel,Maria José (2020)
This paper has two goals: examine the effect of job characteristics proposed in the Job Demands-Control (JDC) model on work-family conflict (WFC) and the effect of this variable on employees mental health; examine the mediate role of WFC between these job characteristics and employees mental health. The hypotheses, using structural equation modeling, were tested with cross-lagged analyses based on two waves over a 6-months period in a sample of 958 employees with different functions in a Portuguese organization from service sector. The findings show that job demands are significant in determining WFC, which in turn mediates the relationship between these job characteristics and employees mental health six months later. No relationship is found between job control and WFC. The paper highlights the relevance to intervene on job demands and WFC to control employees´ mental health.